Transition metal-based high entropy alloy microfiber electrodes: Corrosion behavior and hydrogen activity. (December 2021) - Sarac, Baran; Zadorozhnyy, Vladislav; Ivanov, Yurii P.; Spieckermann, Florian; Klyamkin, Semen; Berdonosova, Elena; Serov, Mikhail; Kaloshkin, Sergey; Greer, A. Lindsay; Sarac, A. Sezai; Eckert, Jürgen
Abstract: This contribution reveals ultra-high corrosion resistance of high entropy alloys (HEAs), i.e. Ti20 Zr20 Nb15 V15 Hf15 Ta15 of 1.85 µm yr –1 in alkaline environment, adverting their use for battery/fuel cell components. Formation of several nanometers passive oxide layer confirmed by scanning transmission electron microscopy accounts for corrosion resistance which increases with TiO x content. Cathodic Tafel slope of 67 mV dec –1 and large transfer coefficient of 0.82 obtained for Ti20 Zr20 Nb20 V20 Ta20 suggest its use for hydrogen electrocatalysis. High amounts of hydrogen storage, 1.7 wt% in Ti25 Zr25 Nb15 V15 Ta20, were confirmed by gas-solid reactions. This HEA also has high corrosion resistance in acidic and saline environments ideal for coatings and surgical tools/implants. Graphical Abstract: ga1 Highlights: Ultra-high corrosion resistance down to 1.85 µm yr –1 of TiZrNbVTa(Hf) HEAs in 1 M KOH. Formation of a few nanometers passive oxide layer accounts for corrosion stability. High hydrogen activity due to low cathodic Tafel slope & large transfer coefficient. Gas-solid reactions confirm high hydrogen storage of 1.7 wt%. High corrosion stability in 0.5 M H2 SO4 (0.148 mm yr –1 ) & 0.9 wt% NaCl (0.081 mm yr –1) .